Effect of potassium fertilization on growth indices, yield attributes and economics of dry direct seeded basmati rice (Oryza sativa L.) - S, Vijayakumar; Kumar, Dinesh; Shivay, YS; Anand, Anjali; P, Saravanane; S, Poornima; Jinger, Dinesh; Singh, Nain (ORYZA-An International Journal of Rice, 2019)
Two-year field experiment was conducted during rainy (kharif) seasons of 2015 and 2016 at ICAR-Indian Agricultural Research Institute, New Delhi to evaluate the effect of potassium (K) fertilization on growth indices, yield attributes and economicsof the dry direct seeded basmati rice. Application of recommended dose of K (60 kg ha-1) half at basal and remaining half at panicle initiation increased the grain yield (5.4 tha-1), net returns (Rs. 85,000 ha-1) and B: C (1.8) ratio by 10, 16 and 20% respectively, over applying the entire amount of K as basal. Significant positive correlation was observed between yield attributes [total tillers(r2=0.74), effective tillers m-2(r2=0.79)]and grain yield of dry direct seeded basmati rice. The two foliar sprays (1st spray at active tillering, 2nd spray at panicle initiation) of 2.5% potassium nitrate (T6) increased fertile tillers % (93.8%), fertility % (83.5%) and grain yield (4.3 t ha-1) by 5%, 6% and 8% respectively, over T1 (control). In case, K is not available for top dressing then two foliar sprays of 2.5% KNO3 at active tillering and panicle initiation stage is found optimum to obtaining higher net returns (Rs. 85200 ha-1) and return from investment on K (Rs. 19.9 rupee-1). Insufficient supply of K during active tillering and panicle initiation stage, decreased the production of tillers m-2 and conversion of tillers into fertile tillers respectively. Hence, active tillering and panicle initiation stage are most critical for K supply in dry direct seeded basmati rice.